Design Improvement of the Rotary-Pulsation Device by Resonance Phenomena - Samoichuk, Kyrylo; Самойчук, Кирило; Yalpachyk, Volodymyr; Ялпачик, Володимир; Kholobtseva, Iryna; Холобцева, Ірина; Dmytrevskyi, Dmytro; Дмитревський, Дмитро; Chervonyi, Vitalii; Червоний, Віталій (Springer Nature Switzerland, 2024)
Improving designs to increase the energy efficiency of machines and equipment in the food industry is particularly relevant for the current state of the world economy. If the energy consumption for the homogenization process is reduced to 1.5-2.5 kW/h, the total energy consumption in the drinking milk production line will decrease by 40-50%. For such a homogenizer, characteristic options for synchronization of rotation phases and rotor control, which include the ratio of the rotor and crank rotation frequencies, have been analyzed. To increase the efficiency of the milk emulsion dispersion process, based on the sliding speed of the fat globule relative to the milk plasma, the optimal synchronization option has been determined, in which the frequency of pulsations caused by the rotational and oscillatory movements of the rotor is the same. Similar nature of speed changes. This leads to the emergence of pulsation resonance, which increases the amplitude of oscillations, the sliding speed, and, consequently, the degree of dispersion. The speed equation for this mode of operation of the homogenizer has been obtained. Удосконалення конструкцій для підвищення енргоефективності иашин і обладнання в харчовій промисловості є особливо актуальним для сучасного стану світової економіки. Якщо енрговитрати на процесс гомогенізації зменшити до 1,5-2,5 кВт/год, загальні енрговитрати в лінії виробництва питного молока зменшаться на 40-50%. Для такого гомогенізатора проаналізовано характерні варіанти сінхронізації фаз обертання і контроль ротора, які включають співвідношення частот обертання ротора і кривошипа. Для підвищення ефективності процессу диспергування молочної емульсії, виходячи зі швидкості ковзання жирової кульки відносно плазми молока, визначено оптимальний варіант сінхронізації, при якому частота пульсацій, викликаних обертальними та коливальними рухами ротора, однакова. Подібний характер змін швидкості. Це призводить до виникнення пульсаційного резонансу, який збільшує амплітуду коливань, швидкість ковзання, а отже, і ступень дисперсії. Отримано рівняння швидкості для цього режиму роботи гомогенізатора.
Удосконалення конструкції ротаційно-пульсаційного пристрою резонансними явищами
Keywords: design improvement; удосконалення дизайну; homogenization; гомогенізація; rotor-pulse device; роторно-пульсійний пристрій; vibrating rotor; вібраційний ротор; resonance phenomena; резонансні явища; industrial growth; промислове зростання; milk emulsion; молочна емульсія